Influence of Knowledge Management on Employee Performance at Kenya Power and Lighting Company - Golompo, Dida Jattani; Rintari, Nancy; Kanyaru, Ruth (Human Resource and Leadership Journal, 2025)
Purpose: To find out the influence of Knowledge management on employee performance at Kenya Power and Lighting Company. Methodology: The study was conducted in the Mount Kenya region, covering nine counties, and employed a descriptive research design to collect data from 1200 KPLC employees. Simple random sampling was used to select respondents from each of the nine operational clusters within KPLC. Data analysis was performed using SPSS Version 25, with descriptive statistics (frequencies and percentages) for summarizing the data, and multiple regression analysis for examining the relationships between variables. The results were presented in tables to facilitate easy interpretation of the findings. Results: The study established a statistically significant positive relationship between knowledge management and employee performance at Kenya Power and Lighting Company (KPLC). The correlation coefficient of 0.468 indicated a moderate positive relationship between the two variables. The R-squared value of 0.219 demonstrated that knowledge management practices explain 21.9% of the variance in employee performance. The adjusted R-squared value of 0.215 confirmed the model’s reliability even when accounting for additional variables. The regression coefficient (B = 0.504) implies that a one-unit increase in knowledge management leads to a 0.504 unit increase in employee performance. The regression model was statistically significant, with an F-statistic of 30.129 (p < 0.05), thereby confirming that knowledge management is a valid predictor of employee performance at KPLC. These results highlight the importance of structured knowledge-sharing systems in improving efficiency, innovation, and staff productivity in Kenya’s energy sector. Unique Contribution to Theory, Policy, and Practice: This study contributes to knowledge management theory, policy, and practice in public utilities, particularly within KPLC. Theoretically, it supports Social Exchange Theory, emphasizing the role of knowledge sharing in improving performance. Policy-wise, it advocates for integrating knowledge management into human capital development, with platforms like digital repositories and mentorship programs. Practically, it highlights the importance of fostering a culture of collaboration, incentivizing knowledge sharing, and incorporating it into performance appraisals to enhance employee productivity and organizational resilience.